Why the whiteness in Swedish outdoor recreation? : a discourse analysis of gender and ethnicity in Swedish environmental policy and practice - Ågren, Ida Maria (Mia) (SLU/Dept. of Urban and Rural Development, 2016)
As of 2009, Swedish Outdoor Recreation is guided by public policy, pleading for everyone’s equal value and right to experience and be outdoors, regardless of gen der, age or colour (2009/10:238). Given Swedish Outdoor Recreation history of being founded upon the perspectives of a white, male middle class (Sandell, 2009), this opens up for the questions of how the goals of equality are achieved and what ideas about nature, gender and ethnicity are actually being reproduced.